(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In present time,COVID-19 the deadly virus is creating havoc all over the world. Loss of manpower, strength, income sources etc. can be seen everywhere. Out of these some are due to direct effects of this pandemic but others are arised in order to preventive measure taken by govt. like Lockdowns.Due to all this a very great decline is observed in economy of India. Only one sector which help in balancing the status is agriculture sector because it occupies approximate 43 percent of geographical area of India. Agriculture plays important role in building indian economy because it creates 18 percent of GDP in alone. Almost 2/3rd of working population depends on it and it creates 52 percent jobs available in India. Different secondary and tertiary working industries like textiles, sugar, vanaspati, edible oil plantation industries, agro-based cottage industries are only functional on raw material directly received from agriculture sector. Apart from this almost 70 percent of India’s exports are originated from agriculture sector.